Prediction of HIV prevalence among individuals aged 15-49 years in Cameroon using Holt’s linear method - Dr. Smartson. P. NYONI; Thabani NYONI (Zien Journals, 2024)
This study uses annual time series data of HIV prevalence among individuals aged 15-49 years for Cameroon from 1990 to 2020 to predict future trends of HIV prevalence over the period 2021 to 2030. The study utilizes Holt’s linear method. The optimal values of smoothing constants α and β are 0.9 and 0.2 respectively based on minimum MSE. The results of the study indicate that annual HIV prevalence among individuals aged 15-49 years will continue to decline over the out of sample period. Therefore, policy makers are encouraged to scale up HIV case detection, prevention and treatment particularly among key populations and vulnerable groups in the society.
Keywords: Exponential smoothing; Forecasting; HIV prevalence